CONTOS ALINHAVADOS: A participação de Machado de Assis em periódicos de moda e literatura - Silveira, Daniela Magalhães da (Outros Tempos: Pesquisa em Foco - História, 2011)
This article examines Machado de Assis’ participation in two articulated publications aimedat the female readers: the Jornal das Famílias and A Estação. In a period of implementation and thegrowing number of newspapers and magazines published in Brazil, winning the readers seemed to be agood strategy. Some recognized names of our literature were very committed to writing for and aboutwomen. Early in his career Machado de Assis published a considerable number of short stories for the"gentle readers". This study suggests some possible meanings to Machado as a writer in the body ofcontributors from fashion journals and literature. We observe, therefore, as these journals were alsoinfluenced and marked the trajectory and paths chosen by the writer.